Pengaruh Pendidikan Gizi Kepada Ibu Terhadap Konsumsi Makanan Dan Status Gizi Anak Balita Penerita Tuberku - Perpustakaan UGM, i-lib ([Yogyakarta] : Universitas Gadjah Mada, 2004)
Background: Tuberculosis is an infectious disease that persists as a public health problem in Indonesia. The tuberculosis infected to the under 5-years old-children namely primary tuberculosis, could decrease the children's immunity eventually causes death, which were 100.000 death rate 75% are children's. condition of children's health were deeply depending on the quality and quantity of their food consumption. An adequate consumption is needed to increase their nutrition status. To improve the maternal behavior of children's food consumption, it is necessary to give nutritional education. Purpose: The purpose of this study is to examine the effect of nutritional education on the food consumption and nutrition status of the under 5-years old-children that infected by primary tuberculosis. Research Method: The research was an experimental research using randomized controlled trial method. The subject was 1 to 5-year(s) old-children those who infected by primary tuberculosis at Unit Rawat falan RSUP Dokter Kariadi Semarang. Two groups chosen by randomized got different treatments, i.e. availability and unavailability of nutritional education. Each group was asked to come to Poliklinik Paru Anak every two-weeks for two months (4 times). The food consumption data was collected by multiple recall before treatment and after research. The nutrition status was determined by weight per age and weight per height ofZ-Score WHO NCHS. Result: The result of this study showed that after the nutritional education issued, the energy consumption average of children has increase 18.18% from necessity and the protein consumption average of children has increase 21.39% from necessity. There was a significant effect of nutritional education on increasing protein consumption of under 5-years old-children that was infected by primary tuberculosis (p